Lipid Systems for the Delivery of Amphotericin B in Antifungal Therapy - Célia Faustino; Lídia Pinheiro (MDPI AG, 2020)
Amphotericin B (AmB), a broad-spectrum polyene antibiotic in the clinic for more than fifty years, remains the gold standard in the treatment of life-threatening invasive fungal infections and visceral leishmaniasis. Due to its poor water solubility and membrane permeability, AmB is conventionally formulated with deoxycholate as a micellar suspension for intravenous administration, but severe infusion-related side effects and nephrotoxicity hamper its therapeutic potential. Lipid-based formulations, such as liposomal AmB, have been developed which significantly reduce the toxic side effects of the drug. However, their high cost and the need for parenteral administration limit their widespread use. Therefore, delivery systems that can retain or even enhance antimicrobial efficacy while simultaneously reducing AmB adverse events are an active area of research. Among those, lipid systems have been extensively investigated due to the high affinity of AmB for binding lipids. The development of a safe and cost-effective oral formulation able to improve drug accessibility would be a major breakthrough, and several lipid systems for the oral delivery of AmB are currently under development. This review summarizes recent advances in lipid-based systems for targeted delivery of AmB focusing on non-parenteral nanoparticulate formulations mainly investigated over the last five years and highlighting those that are currently in clinical trials.